Numerical and Experimental Investigation of the Aerodynamic for the IceWind Blades VAWT - Kadhim H. Suffer,; Yousif Abed Saleh Saleh, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The main aim of the present work is the numerical and experimental investigation carried out in, for the IceWind blade type with two heights (Model 1=250 mm) and (Model 2=125 mm). In this study a computational fluid dynamic CFD is used to simulate the aerodynamic characteristics modelled medals at 10 m/s. The finite volume method and SST (k-ω) turbulent model were used in this simulation. In the experimental part the models are manufactured by three dimensions printing machine (3D printing) using Polylactic acid (PLA), and the experimental work was implemented by using low speed wind tunnel that is available at University of Baghdad/College of Engineering/Mechanical Engineering Department/Fluid Mechanics Laboratory. The finding results from the numerical simulation show that the maximum static pressure at (Model 1) was 69.39 (pa) and the maximum velocity was 13.5 (m/s). For (Model 2) it was 62.58 (pa) and the maximum velocity was 12.69 (m/s). The minimum static pressure at (Model 1) was -66.69 (pa) and the minimum velocity was 1.04 (m/s). For (Model 2) it was -47.94 (pa) and the minimum velocity was 0.98 (m/s). The experimental results showed that (Model 1) give high performance in comparison with (Model 2) , because rotational speed 610 RPM and the power coefficient was 0.0688 also the tip speed ratio was 0.4533, when (Model 2) give rotational velocity were 265 RPM and the power coefficient was 0.03551 also the tip speed ratio was 0.2601.
Keywords: Wind Energy; VAWT; IceWind turbine; CFD; Wind tunnel